A composição urbana em corpos informáticos - Terraza, Cristiane Herres (2019)
The article presents two recent works of Corpos Informáticos, a collective of artists that also constitutes itself as a research group attached to the Universidade de Brasilia. The presentation and reflection on such works provide the knowledge of a few principles that guide the group’s proposals and its questions about the nature of art